2005
DOI: 10.2337/diabetes.54.9.2685
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mfn2, the Charcot-Marie-Tooth Neuropathy Type 2A Gene, in Human Skeletal Muscle

Abstract: The primary gene mutated in Charcot-Marie-Tooth type 2A is mitofusin-2 (Mfn2). Mfn2 encodes a mitochondrial protein that participates in the maintenance of the mitochondrial network and that regulates mitochondrial metabolism and intracellular signaling. The potential for regulation of human Mfn2 gene expression in vivo is largely unknown. Based on the presence of mitochondrial dysfunction in insulin-resistant conditions, we have examined whether Mfn2 expression is dysregulated in skeletal muscle from obese or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
233
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(269 citation statements)
references
References 65 publications
28
233
4
4
Order By: Relevance
“…Here, we demonstrate that Mfn2 deficiency in mice induces susceptibility to develop insulin resistance in response to both age and HFD treatment. These data fit with the observations that muscle Mfn2 is repressed in human obesity or in type 2 diabetes (13,14) and allow us to propose that Mfn2 is a regulator of in vivo insulin sensitivity and a potential target in diabetes drug development.…”
Section: Mfn2 Deficiency Causes Er Stress and Activates Jnk In Liver Andsupporting
confidence: 61%
See 1 more Smart Citation
“…Here, we demonstrate that Mfn2 deficiency in mice induces susceptibility to develop insulin resistance in response to both age and HFD treatment. These data fit with the observations that muscle Mfn2 is repressed in human obesity or in type 2 diabetes (13,14) and allow us to propose that Mfn2 is a regulator of in vivo insulin sensitivity and a potential target in diabetes drug development.…”
Section: Mfn2 Deficiency Causes Er Stress and Activates Jnk In Liver Andsupporting
confidence: 61%
“…Mfn2 is relevant in human disease, and mutations in Mfn2 have been reported in patients affected by Charcot-Marie-Tooth neuropathy type 2A (10)(11)(12). In addition, we have reported that Mfn2 expression is reduced in skeletal muscle of obese subjects and in type 2 diabetic patients (13,14).…”
mentioning
confidence: 68%
“…Muscle mitochondria from patients with type 2 diabetes show reduced size, reduced activity of the electron transport chain and reduced ADP-stimulated and maximal mitochondrial respiratory capacity [1,36,37]. In parallel, type 2 diabetes is associated with reduced expression of genes of oxidative metabolism as well as with repression of MFN2 [38][39][40]. In skeletal muscle of non-diabetic individuals with a family history of type 2 diabetes, decreased expression of nuclear genes encoding proteins of oxidative phosphorylation has been reported [39,40], along with reduced in vivo oxidative phosphorylation [35,41].…”
Section: Discussionmentioning
confidence: 99%
“…In liver and cardiovascular cells, this high glucose-induced fission and rise in ROS production was mediated by increased intracellular calcium levels and ERK1/2-dependent Drp1 phosphorylation (Yu et al, 2011), whereas in muscle cells under chronic hyperglycemia the mitochondrial fragmented state was associated to a decrease in Mfn2 (Bach et al, 2003;Bach et al, 2005). Decreased mitochondrial fission due to FIS1 down-regulation also induced sublethal stress associated to mitochondrial elongation, loss of mitochondrial potential and increased ROS levels (Lee et al, 2004).…”
Section: The Feedback Loop Between Ros Production and Mitochondrial Dmentioning
confidence: 99%